Analysis of workload generated in the two years following first consultation by each new cancer patient: studying the past to plan the future of cancer care - SK. Garattini; F. Valent; AM. Minisini; C. Riosa; C. Favaretti; L. Regattin; G. Fasola (BMC, 2022)
Abstract Introduction Prevalence of cancer patients is dramatically increasing. We aimed at quantifying the oncology workload generated by each new cancer patient in the two years following first consultation. Methods In this record-based retrospective study, we retrieved data of all newly diagnosed patients treated at the Oncology Department of Udine Academic Hospital between 01.01.2012 and 31.12.2017. We calculated mean number and standard deviation of the activity type generated by each new cancer patient during the following 2 years. Results Seven thousand four hundred fifty-two cancer patients generated a total of 85,338 clinical episodes. The two-years mean number of oncology episodes generated was 11.31 (i.e., for every 1,000 new cancer patients, 11,310 oncology activities are generated overall in the following two-year lapse). Patients with advanced disease generated the highest workload (24.3; SD 18.8) with a statistically significant difference compared to adjuvant and follow-up patients (p < 0.001). The workload generated in the period 0-6 and 0-12 months was significantly higher than in the following months (p < 0.001) and it was also higher for patients initially designated to treatment (p < 0.001). Conclusion This is the first study reporting on the mean oncology workload generated during the 2 years following first consultation. Workload is the highest for patient with advanced disease, especially in the first months and in patients in active treatment. A detailed analysis of workloads in oncology is feasible and could be crucial for planning a sustainable framework for cancer care in the next future.